Digital media in education - Cannon, Michelle (Palgrave Macmillan, 2018)
This book argues for dynamic and relevant school experiences for primary and early secondary learners that embed digital media production. It proposes a vision of literacy that combines new technologies with multiple modes of meaning-making. Drawing on theories related to cultural studies, media literacy, anthropology, and creativity, the author explores learning strategies with digital media based on an empowering, values-driven framework. The book advances innovative teaching methods, critiquing educational ‘reforms’ that marginalise media and fail to engage with the complex tensions and textures of modern pedagogy. Positioning film and media-making as vital practices in schools that nurture the skills, dispositions and competencies of modern literacy, the model foregrounds connections between human agency, cognition, and creative practice. This innovative book will appeal to students and scholars of creativity, digital media production, primary education and literacy
9783319783031
Keywords: E-Learning; Bildungstechnologie; B; Technology and Digital Education; Creativity and Arts Education; Educational Technology; Literaturwissenschaft; Literature and Technology/Media; Hardcover; Softcover / Pädagogik/Allgemeines; Lexika; Educational technology; Education; Literacy; Technology in literature; Technology; Digital; Learning; Schools; Media education; primary education; literacy; digital media